2020
DOI: 10.3390/publications8010009
|View full text |Cite
|
Sign up to set email alerts
|

Use of Data Analysis Methods in Dental Publications: Is There Evidence of a Methodological Change?

Abstract: Objectives: To evaluate how data analysis methods in dental studies have changed in recent years. Methods: A total of 400 articles published in 2010 and 2017 in five dental journals, Journal of Dental Research, Caries Research, Community Dentistry and Oral Epidemiology, Journal of Dentistry, and Acta Odontologica Scandinavica, were analyzed. The study characteristics and the reporting of data analysis techniques were systematically identified. Results: The statistical intensity of the dental journals did not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…To the best of our knowledge, this is the first use of machine-learning algorithms to predict complete and incremental tooth loss based on socioeconomic and medical health characteristics [22]. In this study, we used national data to develop and test the performance of five…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first use of machine-learning algorithms to predict complete and incremental tooth loss based on socioeconomic and medical health characteristics [22]. In this study, we used national data to develop and test the performance of five…”
Section: Discussionmentioning
confidence: 99%
“…Letters, brief reports, case reports, narrative reviews, and editorials were excluded from our sample. The sub-field of dentistry and oral health was chosen because we had previously analysed dental journals and studied the application of statistical techniques and quality of reporting in those journals [ 15 , 26 , 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Adequate evaluation of statistical reporting and data presentation during the submission stage improves the quality of biomedical articles and journals [ 9 , 10 , 11 , 12 ]. Previous studies have shown that statistical information is reported more detailly, comprehensively, and usefully in eminent medical journals [ 13 , 14 , 15 ]. This is consistent with their detailed guidelines for authors, as well as a more strict review process, including extensive statistical reviewing [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging complex computational methods can provide impressive prediction models. However, it is unclear how widely these methods are applied in different medical domains [10,11]. This Special Issue includes four articles that focus on these predictive methods.…”
Section: Complex Machine Learning and Deep Learning Predictive Algorithmsmentioning
confidence: 99%